2021
DOI: 10.1016/j.celrep.2021.109269
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression by FEZF2 restricts alternative identities of cortical projection neurons

Abstract: Highlights d FEZF2 specifies subtype-specific fates in newly born neurons d FEZF2 functions as a transcriptional repressor to specify cell fate d FEZF2 specifies cell fates by repressing alternate cell-typespecific genes d FEZF2 and TLE4 are co-repressors in corticothalamic projection neurons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 55 publications
(103 reference statements)
8
54
0
Order By: Relevance
“…(5) similarly, TF repression of alternative neuron-type effector genes during terminal differentiation has been widely reported (Baum et al, 1999;Borromeo et al, 2014;Gordon & Hobert, 2015;Kerk et al, 2017;Remesal et al, 2020;Smith, O'Brien, et al, 2013;Tsyporin et al, 2021;Zheng et al, 2018) and ( 6), finally, active repression of alternative fates in mature neurons has also been observed. Adult removal of Nrl bZIP TF, a TF required for rod photoreceptor terminal differentiation, produces loss of rod effector gene expression, concomitant de-repression of cone effector genes, including two cone opsins, and acquisition of some morphological and electrical properties of cone cells (Montana et al, 2013).…”
Section: The Prevalence Of Repression In the Establishment Of Neurona...mentioning
confidence: 84%
“…(5) similarly, TF repression of alternative neuron-type effector genes during terminal differentiation has been widely reported (Baum et al, 1999;Borromeo et al, 2014;Gordon & Hobert, 2015;Kerk et al, 2017;Remesal et al, 2020;Smith, O'Brien, et al, 2013;Tsyporin et al, 2021;Zheng et al, 2018) and ( 6), finally, active repression of alternative fates in mature neurons has also been observed. Adult removal of Nrl bZIP TF, a TF required for rod photoreceptor terminal differentiation, produces loss of rod effector gene expression, concomitant de-repression of cone effector genes, including two cone opsins, and acquisition of some morphological and electrical properties of cone cells (Montana et al, 2013).…”
Section: The Prevalence Of Repression In the Establishment Of Neurona...mentioning
confidence: 84%
“…Superior to standard DEX analyses that are based solely on expression levels, PGA identifies genes not only by up- or downregulation between conditions, but also with nonrandom patterns along pseudotime, which we refer to as “association.” We identified ten genes that were specifically associated with trisomic cells in ExN4 including ephrin type-A receptor 3 ( EPHA3) and myocyte enhancer factor 2C ( MEF2C ), which have been shown to function in motility and migration during neural development ( Figure 4G, Table 1 and Supplemental Figure 7) . Among the genes unassociated with trisomic cells in ExN4 were several neuronal transcription factors such as BCL11B and FEZF2 , as well as protocadherins, PCDH17 and PCDH19 , all of which play key roles in cortical development ( Figure 4G, Table 1 and Supplemental Figure 7 ) (Chang et al, 2018; Du et al, 2021; Hoshina et al, 2021; Sadegh et al, 2021; Tsyporin et al, 2021). To validate the findings from scRNA-seq, we examined the protein expression of deep and superficial cortical layer markers, BCL11B (CTIP2) and SATB2, respectively in CS.…”
Section: Resultsmentioning
confidence: 99%
“…The postmitotic accumulation of H3.3 coincided with an important period of molecular identity acquisition for new neurons (50-61). To determine whether H3f3a / H3f3b co-deletion affected the developmental establishment of the transcriptional landscape, we intersected genes that were significantly downregulated (579), upregulated (369), or unchanged (3128, FDR > 0.9, -0.1 < log 2 FC < 0.1, log 2 CPM > 1) in dKO-N with ENCODE wildtype forebrain expression data from E10.5 to P0 (62).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have identified a number of key transcription factors that function postmitotically to specify the identities of new cortical neurons (50-61). We find that postmitotic co-deletion of H3f3a and H3f3b (dKO-N) abrogates de novo H3.3 accumulation during this critical period, and alters the deposition and removal of H3 PTMs H3K4me3 and H3K27me3, thus disrupting the establishment of the chromatin landscape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation